2020
DOI: 10.3390/nu12092678
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Potential Interaction of Selenium and Iodine on Placental and Child Health

Abstract: A healthy pregnancy is important for the growth and development of a baby. An adverse pregnancy outcome is associated with increased chronic disease risk for the mother and offspring. An optimal diet both before and during pregnancy is essential to support the health of the mother and offspring. A key mediator of the effect of maternal nutrition factors on pregnancy outcomes is the placenta. Complicated pregnancies are characterized by increased oxidative stress in the placenta. Selenium and iodine are micronu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 161 publications
0
15
0
Order By: Relevance
“…For all these reasons, Se is recognized as an essential element to human reproduction. In humans it reduces the time to conceive and improves fertility [ 50 ], decreases the risk of hypertension and other pregnancy complications in pregnant women [ 51 , 81 , 82 , 83 , 84 ], and balances important inflammatory indicators such as C-reactive protein and the antioxidant defense system [ 82 , 83 , 85 ]. Furthermore, Se deficiency affects health parameters in children like growth and development, as well as cognitive functions of infants in the first few years of life [ 86 , 87 , 88 ].…”
Section: Selenium During Preconception Gestation and Lactationmentioning
confidence: 99%
“…For all these reasons, Se is recognized as an essential element to human reproduction. In humans it reduces the time to conceive and improves fertility [ 50 ], decreases the risk of hypertension and other pregnancy complications in pregnant women [ 51 , 81 , 82 , 83 , 84 ], and balances important inflammatory indicators such as C-reactive protein and the antioxidant defense system [ 82 , 83 , 85 ]. Furthermore, Se deficiency affects health parameters in children like growth and development, as well as cognitive functions of infants in the first few years of life [ 86 , 87 , 88 ].…”
Section: Selenium During Preconception Gestation and Lactationmentioning
confidence: 99%
“…Maternal Se status regulates Se levels in the neonate, and maternal circulating Selenop is responsible for placental Se transport [ 18 , 39 , 40 , 41 , 42 ]. Understanding of specific neonatal selenoproteins expression in response to maternal Se deficiency may provide insight into mechanisms by which Se deficiency is associated with worse outcomes in the neonatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium (Se) is an essential trace element in the human body [1]. It is transferred to the fetus through the placenta and plays an important role in pregnancy [2]. Several epidemiological studies have shown that low levels of Se in pregnancy may be associated with miscarriage, preterm birth, neural tube defects (NTDs), preeclampsia, and other maternal gestational complications [3][4][5][6][7], as well as with impact on the cognitive function of the infant [8].…”
Section: Introductionmentioning
confidence: 99%
“…Selenoproteins are vital to maternal and infant health, and they contribute to antioxidation, immunoregulation, and antagonism [10]. The demand for Se significantly increases during gestation [2], and with the development of pregnancy, Se levels in serum gradually decline due to the active transport of Se to the placenta and hemodilution [11]. There is evidence to suggest that suboptimal Se intake during pregnancy is a common phenomenon [12].…”
Section: Introductionmentioning
confidence: 99%